HYDATID CYST PRESENTING AS A THYROID NODULE:REPORT OF THREE CASES - Mohammad-Hassan Bastanhagh; Vahab Fatourechi; Reza Rajabian (Acta Medica Iranica, 1995)
Hydatid cyst of the thyroid gland is rare, even in areas where echinococcosis is endemic. We report two cases of hydatid cyst of the thyroid gland and one case of a hydatid cyst in the soft tissues of the neck, in the latter, the cyst was superimposed on the thyroid gland and presented as a thyroid nodule. In one patient, fune needle aspiration biopsy produced severe anaphylaxis. In view of the rare occurrence of hydatid disease of the thyroid gland, fune needle aspiration biopsy of thyroid nodules can be performed routinely in areas enderric for echinococcosis but should be avoided if hydatid disease is strongly suspected.